The IBNET Water Supply and Sanitation Performance Blue Book - van den Berg, Caroline; Danilenko, Alexander (World Bank, 2012)
The International Benchmarking Network for Water and Sanitation Utilities (IBNET) blue book creates a baseline and, at the same time, offers a global vision of the state of the sector in developing countries. By tracking progress in and quantifying and assessing the water supply and sanitation sectors, IBNET helps meet the goal of providing safe, sustainable, and affordable water and sanitation for all. This report serves three purposes. First, it aims to raise awareness of how IBNET can help utilities identify ways to improve urban water and wastewater services. Second, it provides an introduction to benchmarking and to IBNET's objectives, scope, focus, and some recent achievements. Third, it elaborates the methodology and data behind IBNET and presents an overview of IBNET results and country data. By providing comparative information on utilities' costs and performance, IBNET and this study can be used by a wide range of stakeholders, including: 1) utilities: to identify areas of improvement and set realistic targets; 2) governments: to monitor and adjust sector policies and programs; 3) regulators: to ensure that adequate incentives are provided for improved utility performance and that consumers obtain value services; 4) consumers and civil society: to express valid concerns; 5) international agencies and advisers: to perform an evaluation of utilities for lending purposes; and 6) private investors: to identify opportunities and viable markets for investments.